Eko teknologi untuk pencegahan kebakaran pada lahan gambut di Desa Rimbo Panjang, Kecamatan Tambang, Kampar - Saktioto Saktioto; Ari Sulistyo Rini; Rahma Dewi; Deprianto Deprianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Riau, 2019)
Peatland fires can cause emist GHG identification in Rimbo Panjang village, Tambang sub-district, Kampar whre there are community complaints about environmental conditions or smog. The purpose of this activity is to implement the technology of fire prevention on peat land in Rimbo Panjang Village, Tambang District, Kampar Regency, Riau Province. The method applied is Eco Technology with a solidification system which means reducing the pores of peat so that it can extinguish the fire quickly. The other method used is by blocking fire contact with outside air (oxygen) that is by watering using a mixture of detergent. The results obtained from this activity showed that based on the water table on peatland it was found to be varied and included in the category of deep peat, only a small portion in village 1 found a water table at a depth of 20 cm. Based on the condition of the clay layer it also turns out to be found in depths between 2.5 m to 6 meters. Based on the results of observations in the field, the condition of peat in Rimbo Panjang is vulnerable to fire. Fire simulations that have been carried out by making artificial peat conditions which are then combusted show that the Eko Technology method has been able to fire out peatlands quickly.